Evaluation of Electronic Translation Tools Through Quality Parameters - Kučiš, Vlasta; Klasnić, Ksenija, sociologinja; Seljan, Sanja (2009)
In the paper, the difference of translation quality of texts obtained through traditional reference works and online electronic translation tools (corpus and multilingual terminology database) will be measured in three main categories: lexical, orthographic and punctuation ; syntatically and stylistically using paired samples t-tests.
Projekt MZOS
ENG